Desempenho de cordeiros lactentes recebendo probióticos em comedouros privativos - Pinheiro, Rafael S.B. [UNESP]; Sobrinho, A. G S [UNESP]; Yamamoto, S. M. (My University, 2007)
The presente study was carried out to evaluate the performance of 40 lambs 7/8 Ile de France 1/8 Ideal (20 not castrated males and 20 females) raised with access to creep feeding, until get 17 kg of corporeal weight. The animals were divided in treatments, receiving isoproteic and isoenergetic diets, with diferent levels of probiotics (D1=0%, D2=0,8% e D3=12%). They were analysed in regart to born weight, weight at 30 days and weight gain at maternal independent (from 1th to 4th weeks) and maternal independent (from 5th to 8th week), the age of wean and daily weight gain. The average intake of dry matter by the lambs at D1, D2 and D3 was 0,27, 0,26 and 0,27 kg/day, respectively. On maternal dependent phase, there was no interaction and differences between diet and sex in the born weight (3.30 kg), weight at 30 days of age (11.79 kg) and in the average daily weight gain (0.28 kg). On maternal independent phase, there were no differences in the age of weam (53 days) and daily weight gain (0,26 kg) between diet and sex. It was concluded that probiotics inclusion in the diet of the suckling lambs (males not castrated and females) didn't improve their performance.
Performance of lambs receiving probiotics in creep feeding
Keywords: Growth promoter; Intake; Lambs; Weight gain; Animalia; Ovis aries